Depression and the risk of fibromyalgia syndrome: a two-sample Mendelian randomization study - Ma, Xiaoshan; Sun, Jing; Geng, Ren; Zhao, Yao; Xu, Wanzhen; Jiang, Yining; Zhao, Liyan; Li, Yunqian (Frontiers in Psychiatry, 2024)
BackgroundFibromyalgia (FM) is a common illness with a wide range of symptoms, mainly manifested by unexplained chronic systemic musculoskeletal pain, sleep disorders and fatigue, sometimes accompanied by cognitive impairment, psychiatric symptoms and autonomic dysfunction. Previous studies have indicated a correlation between depression and the risk of FM; however, it remains uncertain whether this association reflects a causal relationship.MethodsWe evaluated the etiological association between the genetically predicted depression and the risk of developing FM by conducting a two-sample Mendelian Randomization (MR) study. The data on single nucleotide polymorphisms (SNPs) related to depression were obtained from the UK Biobank (UKB) and the Psychiatric Genomics Consortium (PGC) of White British European ancestry, and the data for FM were from the 5th release of the FinnGen study. We adopted the Inverse Variance Weighted (IVW) approach as the principal standard. In order to detect the existence of horizontal pleiotropy and heterogeneity, we adopted the MR-Egger approach as the sensitivity analysis.ResultsIn our MR analysis, 42 depression-related variants were identified as valid instrumental variables (IVs). The IVW approach’s results manifest that there is no etiologic causality between genetically predicted depression and the risk of FM (odds ratio [OR]: 1.673, 95% confidence interval [CI]: 0.852—3.287, P = 0.135). The study did not find any significant heterogeneities or horizontal pleiotropies (P > 0.05).ConclusionsOur results suggest that there is no significant genetic evidence linking depression to an increased risk of FM. However, further research is necessary to investigate the potential relationship and underlying mechanisms between depression and the risk of FM.